Culture in Crossroads: Architecture of Natha Devalaya of Kandy, Sri Lanka - Ahilan, P. (Education Plus, 2022)
Natha Deviyo is Kandiyan national guardian deity, connected with the Bodhisattva cult of Mahayana Buddhism and transformed into the next Buddha Maître. The cult of Natha was popularized and established in the Kandyan era (15th CE to 18th CE) in Sri Lanka. One of the first Devalaya for the god Natha is situated in front of the Temple of tooth relic at Kandy. The architecture of Natha Devalaya represents Dravidian architecture of South India in its form with Vimana, Eddupattai pillar with the motifs of Dravidian architecture. This architectural format questions the authentic Arya - Sinhala Theravada Buddhist nationalist hegemonic claim of the Sri Lankan state and the historical narrations of Sri Lanka. Because of the architecture of 'Arya' is Nagara style and the North Indian origin. This also suggests the possibilities of the shared cultural past and memories of connected communities and ethnicities in terms of accommodation and assimilation of diverse cultures.